Diclofenac induced gastrointestinal and renal toxicity is alleviated by thymoquinone treatment. (August 2018) - Aycan, İlker Öngüç and Elpek, Özlem and Akkaya, Bahar and Kıraç, Ebru and Tuzcu, Hazal and Kaya, Sabriye and Coşkunfırat, Nesil and Aslan, Mutay
Abstract: The aim of this study was to investigate whether thymoquinone (TQ) could alleviate diclofenac (DCLF)-induced gastrointestinal and renal toxicity in rats. Diclofenac was administered via intramuscular injection twice daily for 5 days and TQ was given by gavage for the same period. Hematological and biochemical profiles were measured with autoanalyzers while reactive oxygen/nitrogen species (ROS/RNS) generation and total antioxidant capacity (TAC) were assayed by standard kits. Tissue injuries were evaluated by microscopy and histopathological scoring. Diclofenac treatment caused kidney and liver function test abnormalities, reduced hematocrit and hemoglobin levels but increased WBC and platelet counts. Histopathological findings showed renal tubular damage, gastrointestinal lesions and increased fibrosis in DCLF treated rats. Thymoquinone administration, along with DCLF treatment, attenuated hematological test abnormalities and DCLF induced renal functional impairment as evident by significantly restored serum creatinine and blood urea nitrogen levels. Similarly, TQ treatment significantly alleviated liver function test abnormalities and decreased tissue injury in the stomach and duodenum. Diclofenac treatment caused increased ROS/RNS formation and decreased TAC in the kidney, stomach and duodenal tissue. Thymoquinone administration increased gastrointestinal and renal TAC in DCLF treated rats. These results indicate that TQ could ameliorate gastrointestinal and renal toxicity induced by high dose DCLF treatment. Highlights: Thymoquinone treatment alleviates diclofenac-induced gastrointestinal toxicity. Thymoquinone treatment alleviates diclofenac-induced renal toxicity. Thymoquinone attenuates diclofenac-induced hematological test abnormalities. Thymoquinone attenuates diclofenac-induced liver function test abnormalities. Thymoquinone could ameliorate toxicity induced by high dose diclofenac treatment.